Warranties for Battery Energy Storage Systems in Developing Countries - Energy Sector Management Assistance Program (World Bank, Washington, DC, 2020)
In developing countries, battery storage is becoming a viable way to increase system flexibility and enable more integration of variable renewable energy. Battery energy storage systems (BESS) respond rapidly to control signals, are easy to deploy, and are benefiting from cost reduction trends. New battery technologies have valuable attributes that are well suited to the needs of developing countries. However, they have a rather short track record in terms of deployment and operation, and this can hamper efforts to reassure buyers and investors that these new technologies will perform reliably over their project life. Conditions found in some developing countries may present extra challenges as energy storage systems need to operate in harsh climate conditions, often in remote locations with limited data access. Warranties for BESS provide mechanisms for buyers and investors to mitigate the technical and operational risks of battery projects, by transferring the risk of a manufacturing defect or performance issues to the manufacturer or the battery vendor. Warranties are used in the same way for traditional generation technologies, such as solar photovoltaic (PV) and wind.